Logros de aprendizaje y aprendizaje significativo en el área de desarrollo personal, ciudadanía y cívica en estudiantes de la Institución Educativa 584002 CRFA Santa Teresa primera zona río Yavarí 2022 - Chuquipiondo Vela, Marco Antonio (2024)
Determine the relationship between learning achievements and significant learning in the area of Personal Development, Citizenship and Civics in students of Educational Institution No. 584002 CRFA “Santa Teresa” first zone of the Yavarí River 2022, was the objective of the research. Two questionnaires were administered to 142 students from first to fifth grade of secondary school. Spearman's Rho non-parametric statistical package was used to test the hypothesis. The research concluded that there is a high positive correlation (r = 0.752). In learning achievements, 57.9% of students are "In process", 26.6% reached the expected level and 15.5% remain "In beginning". In meaningful learning, 60.0% progress, 33.7% consolidate goals, and 6.3% require support. Both reflect key advances and challenges at educational levels.